Attitudes to Irish as a school subject among 13-year-olds - Emer Smyth; Merike Darmody (The Economic and Social Research Institute (ESRI), 2016)
The purpose of this study is to investigate the influence of background and school factors on second-level students' attitudes toward Irish as a school subject drawing on the Growing Up in Ireland study. The study focuses on the perceptions of the core subjects, English, Mathematics and Irish, and presents a profile of students who find the Irish language interesting or difficult. The study enables us to investigate the attitudes of teenagers towards the language in a systematic way, including personal, school and other characteristics that may have an impact on attitudes towards the Irish language.
Keywords: 330; post-primary schools; attitude to the Irish language; Growing Up in Ireland survey